European Union Energy Saving Policy - N. Y. Kaveshnikov (MGIMO University Press, 2014)
This article analyses methods of energy efficiency stimulation in the European Union. The author investigates basic areas of the EU activity; in particular, the author estimates results of implementation of the Energy Star program, new provisions of labeling of energy-using products, measures to increase energy efficiency in buildings. The paper also analyzes the provisions of the Directive 2012/27 that is the first EU document, providing for a comprehensive approach to energy saving at all stages: production, transformation and consumption. Today EU policy includes: 7) a general political and regulatory framework laid down by the European action plan on energy efficiency and Directive 2012/27; 2) national action plans on energy efficiency, which should be in line with indicative targets set at the EU level; 3) special EU documents in key areas of energy efficiency (buildings, energy-consuming equipment etc.); 4) accompanying instruments, such as target funding, information dissemination, support of specialized networks. The paper gives a comprehensive analysis of the key methods of implementation of EU policy in the area of energy saving. The author concludes that EU operates within the framework of the open method of coordination. The system of mandatory/voluntary technical standards has allowed to achieve significant success, but indicative planning and monitoring of national actions are not completely effective. In the long term EU policy in the area of energy efficiency is restrained by member states unwillingness to delegate to the European Union a more detailed powers in this field and to give the EU bodies facilities to execute more strict control. In the short term - in conditions of economic crisis, the EU countries are not ready to invest significant budget funds in projects with long payback period.